Tribochemistry of damage to metal joints during fretting corrosion - Shevelya, V.V.; Oleksandrenko, V.P.; Dykha, O.V.; Sokolan, K.S. (Problems of Tribology, 2026)
The patterns of fretting wear of a number of structural materials and galvanic coatings were researched, taking into account their mechanical and physicochemical properties. The influence of the composition of the gas environment (air, oxygen) on the intensity of fretting wear was assessed, as well as the contact load with the corresponding temperature recording in the friction zone. Data were obtained indicating the possibility of low-amplitude fretting of metals in an air environment along with the oxidative processes of electrochemical corrosion. The physicochemical prerequisites for the initiation of electrochemical processes in the zone of vibrational contact during the formation of an ultradisperse oxide layer, which becomes a catalyst for the accelerated chemisorption of oxygen and air moisture in radical and ion-radical forms, are considered. As a result, according to the electronic theory of adsorption and catalysis on semiconductors (oxides), contact phenomena begin to develop through the mechanism of autocatalytic corrosion. After a latent period of oxide accumulation, conditions are created for electrochemical processes that contribute to corrosion-fatigue failure of mating surfaces. The results of the study expand existing ideas about the nature of corrosion processes during partial and mixed sliding, focusing on the possibility of using traditional methods of electrochemical protection to increase the fretting resistance of friction units operating under vibration conditions